Barriers to participation in surgical randomized controlled trials in pediatric urology: A qualitative study of key stakeholder perspectives. Issue 3 (June 2016) - Vemulakonda, Vijaya M.; Jones, Jacqueline
Summary: Introduction: Randomized controlled trials (RCTs) are considered the gold standard for assessing treatment efficacy. However, pediatric surgical RCTs have been limited in their ability to recruit patients. The purpose of this study was to identify barriers and motivators to pediatric participation in surgical RCTs. Methods: We conducted a series of two focus groups with parents and one focus group with urology providers for children aged <2 years of age with a diagnosis of Society for Fetal Urology grade 3 or 4 hydronephrosis. We then administered a survey to referring pediatricians based on the initial analysis of focus group findings. Theme analysis was used for all qualitative transcribed text data obtained from focus groups and open-ended survey questions using team-based inductive approaches. Descriptive statistics were obtained for the remainder of the provider survey. Results: Using qualitative text from stakeholders ( n = 38) we identified four key themes across the data : responsibility to my child; responsibility to my patient; responsibility to the field; and irreversibility of surgery . Participants felt there was an obligation to be informed of relevant scientific research within a clinic research culture. However, there remains a disconnect for parents between randomized research studies that may ultimately benefit their child, depending on their age and concern their child is being treated as a 'guinea pig'. Some parents were willing to participate in RCTs but all were more open to participate in an observational study where the treatment decisions were felt to be under their control even when there was no "right answer" or multiple equivalent options for treatment. There was mixed opinion across the parents and providers whether research trial education and enrollment should be provided by the pediatrician or urologist. Active physician decisions were seen as critical within the context of a long term clinical relationship and provision of information of risks and benefits without pressure were considered essential for ethical research by both parents and providers. Conclusion: While some parents are open to participation in surgical RCTs, providers and parents of children with hydronephrosis feel discomfort with the element of chance in surgical randomized trials. Parents and providers are more likely to participate in observational studies where treatment decisions may be made jointly by the physician and the parent. These findings suggest that pragmatic trial strategies with the option for participation in an observational cohort may improve recruitment of pediatric patients into surgical clinical trials. Table Perceived barriers to participation in surgical randomized controlled trials. Parents Pediatric urologists Pediatricians Counseling and decision-making Loss of control over treatment decision Child's inability to participate in decision Discomfort with admission of uncertainty in treatment Time and effort needed for education regarding RCTs Ethics of randomization in young children/lack of patient input into decision Complications and risks Stigma of child being labeled as "sick" Concerns about cost and long term complications Adequacy of safeguards and justification of potential risks Potential risk of sham surgery/anesthesia exposure Risk of side effects, unnecessary tests, and unknown long term consequences Unique attributes of surgery Irreversibility of surgery No difference between medical and surgical RCTs Lack of true equipoise between surgical and non-surgical treatment arms Irreversibility of surgery